Social distance and the structure of stereotypes of primary school students towards Roma: Quantitative and qualitative analysis - Smuđa Marija S.; Luković Slađana R.; Petrović Danijela S. (University of Kragujevac - Faculty of Pedagogy, Užice, 2019)
Social distance has been the subject of numerous research papers; the issue of researching social distance toward Roma is especially important. There are several aims of our study. The basic goal of the research is to determine the existence and intensity of social distance towards Roma held by primary school students. The specific goal of the research is to determine the differences in the presence of social distance held by students who often interact with Roma children, as well as those who rarely interact with them. The research sample consisted of 152 participants (71 fourth-grade students and 81 eighth-grade students; 85 boys and 67 girls). The Bogardus's Scale, modified for children, was used for researching the social distance. Furthermore, the research implied two focus groups for the qualitative data to be obtained. The results showed the existance of social distance toward Roma students. Furthermore, according to this data, the least desirable relationship was sitting in the same school bench with Roma children, whereas the most acceptable relationship was going to the same school with Roma. Moreover, it was established that students having more relationships with Roma had lower social distance toward them as well. Qualitative data analysis shows higher level of negative stereotypes and attitudes toward Roma. It is essential to combine quantitative and qualitative measures for the purpose of getting the unbiased description of social distance toward Roma.